Menelusuri Historisitas Pembentukan Hukum Islam: Menggagas Yurisprudensi Islam Indonesia - Muhammad Yusuf (TSAQAFAH, 2012)
The Islamic law and its existence can not be separated from the socio- historical factors surrounding the scholars of  fiqh in producing islamic law. Variety of  environmental and socio-political context contributed significantly in shaping patterns of Islamic legal thought. In fact, judging from the relationship between the political (power) with the occurance of laws there are a number of  correralion indicators. It is likely a madhhab develop because of  political support. When a madhhab ruling the other madhhab highly susceptible to hard resistance. Indeed, ideally fiqh should be able to provide answers to a variety of  empirical facts on the various issues. And, fiqh in Indonesia should not simply adopt the products of  classical period only, but need to develop and articulate the contemporary context based on the empirical facts. Internal understanding of the diversity of Indonesian Muslims is also a consideration in producing fiqh other than social facts. With the principle of  unity in things agreed, and tolerant of things that are not agreed upon, particularly with regard to the furu’iyat. Fiqh as a product of thought influenced by the socio-historical conditions of  society should not be seen as absolute. Now, need to show that penetrates all aspects of jurisprudence and responded critically on contemporary issues that continue to vary and evolve.